Developing new drugs from annals of Chinese medicine - Zhaoxiang Bian; Shilin Chen; Chungwah Cheng; Jun Wang; Haitao Xiao; Hongyan Qin (Elsevier, 2012)
Developing new pharmaceuticals requires massive amounts of time, money and efforts. The key step is how to find a safe and effective entity for a disease condition and how to develop it as new drug effectively. Unfortunately, the FDA's rate of approving new entities has declined dramatically in the last three decades. There is a strong need to review the current strategy and to optimize process in developing new drugs, both to shorten the process and increase the success rate. Chinese medicine has used natural products to treat patients for thousands of years, and Chinese medicine practitioners have chronicled the patients and treatment methods for thousands of years. There is much information that has not yet been used. The success stories of artimisinin and arsentic trioxide are wonderful examples of how the annals of Chinese medicine can provide leads for discovering new drugs. This paper argues that the annals of Chinese medicine are valuable and describes how they can be used in modern drug discovery. The major topics addressed are: (i) why Chinese medicine is a rich resource for finding new drugs; (ii) how to identify a potential valuable record from Chinese medicine annals; (iii) when a potential valuable record is identified from annals, how to proceed; and (iv) both why and how the approach used for chemical drugs should be revised for drugs based on the historical documents related to herbal medicine. In conclusion, we argue here that the annals of Chinese medicine offer not only a rich resource for new drugs, but also several centuries of patient data with regard to safety and efficacy, that in effect represent pilot studies. Acknowledging and using these data can shorten new drug discovery time and improve efficiency of the drug development process, bringing more effective, safe drugs to market much more quickly and cheaply.